Making room for manoeuvre: addressing gender norms to strengthen the enabling environment for agricultural innovation. Issue 4 (18th May 2020) - Badstue, Lone; Elias, Marlène; Kommerell, Victor; Petesch, Patti; Prain, Gordon; Pyburn, Rhiannon; Umantseva, Anya
ABSTRACT: Local gender norms constitute a critical component of the enabling (or disabling) environment for improved agricultural livelihoods – alongside policies, markets, and other institutional dimensions. Yet, they have been largely ignored in agricultural research for development. This viewpoint is based on many years of experience, including a recent major comparative research initiative, GENNOVATE, on how gender norms and agency interact to shape agricultural change at local levels. The evidence suggests that approaches which engage with normative dimensions of agricultural development and challenge underlying structures of inequality, are required to generate lasting gender-equitable development in agriculture and natural resource management.